Amarant. (Rotterdam : Stichting Groep 7152, 1975)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Prof. Lorentzlaan 147, 3769 GC Soesterberg ; vanaf (1979) 8 : Kerkstraat 32, 4001 MB Tiel
Nederlands
Periodiek